Application of Physiologically Based Pharmacokinetic‐Pharmacodynamic Modeling in Preterm Neonates to Guide Gentamicin Dosing Decisions and Predict Antibacterial Effect. (8th June 2021) - Neeli, Harshith; Hanna, Nazeeh; Abduljalil, Khaled; Cusumano, Jaclyn; Taft, David R.
Abstract: Clinical studies in preterm neonates are rarely performed due to ethical concerns and difficulties associated with trials and recruitment. Consequently, dose selection in this population is primarily empirical. Scaling neonatal doses from adult doses does not account for developmental changes and may not accurately predict drug kinetics. This is especially important for gentamicin, a narrow therapeutic index aminoglycoside antibiotic. While gentamicin's bactericidal effect is associated with its peak plasma concentration, keeping trough concentrations below 1 µg/mL prevents toxicity and also helps to counteract adaptive resistance in bacteria such as Escherichia coli . In this study, physiologically based pharmacokinetic‐pharmacodynamic (PBPK‐PD) modeling was used to support and/or guide dosing decisions and to predict the antibacterial effect in preterm neonates. A gentamicin PBPK model was successfully verified in healthy adults and preterm neonates across all gestational ages. Clinical data from a neonatal intensive care unit at NYU Langone Hospital–Long Island was used to identify dosing regimens associated with increased incidence of elevated gentamicin trough concentrations in different preterm patient cohorts. Model predictions demonstrated that a higher dose with an extended‐dosing interval (every 36 hours) in neonates with a postmenstrual age of 30 to 34 weeks and ≥35 weeks, with postnatal age 8 to 28 days and 0 to 7 days, respectively, were more likely to have a trough <1 µg/mL when compared with once‐daily (every 24 hours) dosing. PBPK‐PD modeling suggested that a higher dose administered every 36 hours may provide effective antibacterial therapy.